MST 564 - Statistical reliability [Kebolehpercayaan Statistik] December 2016 -January 2017 - PPSM, Pusat Pengajian Sains Matematik (2017)
First Semester Examination 2016/2017 Academic Session December 2016/January 2017 Duration : 3 hours